Spiritual symptoms of aged in times of a COVID-19 pandemic - Duque, Paula; Campiño-Valderrama, Sandra Milena; Castañeda-Hidalgo, Hortensia (Horizonte Sanitario, 2022)
Objective: To describe and to correlate the spiritual symptoms presented by the elderly in the municipality of Caldas, Colombia in times of the COVID-19 pandemic. Materials and Method: Quantitative, descriptive, observational study, with 300 elderly people, a validated instrument on spiritual symptoms was applied, with descriptive statistics using Pearson test. Results: spirituality symptoms were moderate in terms of spiritual pain with 34%, self-punishment 35%, projected spiritual search was found to be severe in 36% as well as spiritual anguish 42%, disbelief 45%, hopelessness and heartbreak 48%, statistical significance was found correlating spiritual signs with age, sex, occupation, marital status, illness, presence of children and need for help with daily activities. Conclusions: It is concluded that the results allow describing the spiritual symptoms, as well as making correlations between the symptoms and the various characteristics of the participants. Furthermore, these results allow us to reflect that the care of the elderly must consider, in addition to the biological dimension, the spiritual dimension, showing that care must be taken in a holistic way to improve the health status and quality of life of the elderly Therefore, the problems of the aging process should be considered in its different contexts, and multidisciplinary models and health policies should be proposed that improve the quality and living conditions of this sector of the population and its caregivers. Key words: Spirituality; Aged; Community health nursing